Recent advances in finance for inclusive development: a survey - Simplice A. Asongu; Lieven De Moor (African Governance and Development Institute (AGDI), 2015)
The policy debate has been shifting from the finance-growth nexus to the finance-inequality relationship. In the transition from Millennium Development Goals (MDGs) to Sustainable Development Goals (SDGs), there has been an urgent policy challenge of putting some structure on recent advances in finance for more inclusiveness. The overarching question tackled in this paper is: to what degree has financial development contributed to providing opportunities of human development for those in the low-income strata and by what mechanisms? We survey about 170 recently published papers to provide recent advances in finance for inclusive development. The analytical approach consists of first, situating issues of exclusive growth in the context of the literature and then reviewing recent financial inclusion growth strategies. Developed and developing countries are separately engaged in some currents to account for heterogeneity in financial development benefits. Retained financial innovations are structured along three themes, notably: the rural/urban divide, women empowerment and human capital in terms of skills & training. The financial instruments are articulated with case studies, innovations and investment strategies with particular emphasis, inter alia on: informal finance, microfinance, mobile banking, crowdfunding , Islamic finance, remittances, Payment for Environmental Services (PES) and the Diaspora Investment in Agriculture (DIA) initiative.
Keywords: G20; I10; I20; I30; O10; 330; Finance; Inclusive Growth; Economic Development